Species composition and medicinal uses of mangrove plants in Southwest Aceh, Indonesia - WINTAH WINTAH; MOH. HUSEIN SASTRANEGARA; KISWANTO KISWANTO; ALIN FITHOR (Society for Indonesian Biodiversity, 2026)
Abstract. Wintah, Sastranegara MH, Kiswanto, Fithor A. 2026. Species composition and medicinal uses of mangrove plants in Southwest Aceh, Indonesia. Biodiversitas 27 (3): d270321. https://doi.org/10.13057/biodiv/d270321. Mangrove ecosystems are among the most productive ecosystems in the world, serving ecological, economic, and cultural functions. Mangroves play an important role in maintaining the biological integrity and resources of marine ecosystems. The village of Tadu Raya Sub-district, Nagan Raya District of South West Aceh has a mangrove forest covering 50 ha. The potential of the mangrove forest in this area is enormous, including medicinal plants. This study aims to identify plants with potential as medicines. The study used a survey method, with sampling conducted at three stations with transects perpendicular to the coast at fixed intervals. Vegetation sampling was conducted randomly at each station and repeated three times in 10 x 10 m plots for trees, 5 x 5 m plots for saplings, and 1 x 1 m plots for seedlings. Information on the use of mangroves through investigations of local communities and a review of the scientific literature. The study found nine medicinal plant species, including trees and undergrowth plants: Acanthus ilicifolius, Avicennia marina, Bruguiera gymnorrhiza, Nypa fruticans, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Sonneratia alba, and Sonneratia caseolaris. The local community uses these species as medicine for thrush, toothache, wounds, diarrhea, stomach ache, abdominal pain, bruises, chickenpox, fever, itching, and cough. The highest species importance value (IVI) at Station 1 (ST1) was R. apiculata (54.9%) with relative density (16.67%), relative frequency (18.75%), and relative dominance (19.53%). The highest species importance value (IVI) at Station 2 (ST2) was R. apiculata (56.66%), with relative density (20%), relative frequency (20%), and relative dominance (14.08%). Station 3 (ST3) had the highest species importance value (IVI) of R. mucronata (57.4%) with relative density (20%), relative frequency (20%), and relative dominance (17.35%).